The Predictive Value of Endothelial Inflammatory Markers in the Onset of Schizophrenia - Radu G (Dove Medical Press, 2020)
Gabriela Radu,1,2,* Constantin Luca,3,* Lucian Petrescu,3,* Diana Aurora Bordejevic,2,3,* Mirela Cleopatra Tomescu,1,2 Minodora Andor,1,2 Ioana Cîtu,1,2 Adelina Mavrea,1,2 Valentina Buda,4 Cătălin Tomescu,1,2 Florin Borcan,4 Liana Dehelean5 1Department of Internal Medicine I, Cardiology Clinic, “Victor Babeş” University of Medicine and Pharmacy, Timişoara, Romania; 2City Emergency Hospital Timisoara, Timişoara, Romania; 3Department of Cardiology, “Victor Babeş” University of Medicine and Pharmacy, Timişoara, Romania; 4Department of Pharmacology and Clinical Pharmacy, “Victor Babeş” University of Medicine and Pharmacy, Timişoara, Romania; 5Department of Neurosciences and Psychiatry, “Victor Babeş” University of Medicine and Pharmacy, Timişoara, Romania*These authors contributed equally to this workCorrespondence: Valentina Buda 2 nd E. Murgu Square, Timişoara 300041, RomaniaTel +40755100408Email buda.valentina.oana@gmail.comPurpose: This study aimed to assess the serum levels of intracellular adhesion molecule (sICAM-1), and vascular cell adhesion molecule (sVCAM-1), in the first psychotic episode schizophrenia (SZ) patients, before and after six months of antipsychotic treatment.Patients and Methods: The study included 50 patients with a first hospitalization for SZ and 50 healthy control subjects that were patient-matched regarding age, gender, body mass index and smoking status. The evaluation included the presence of cardiovascular risk factors, measurements of systolic and diastolic blood pressure, body mass index, smoking status, ankle-brachial index, carotid intima-media thickness, and echocardiography. The Brief Psychiatric Rating Scale (BPRS) score was calculated for the patients. The plasma levels of fasting glucose, total cholesterol, LDL-cholesterol, HDL-cholesterol, triglycerides, sICAM-1 and sVCAM-1 were determined at baseline in all subjects and after six months of antipsychotic treatment. Thirty patients (60%) were treated with olanzapine and 20 (40%) with risperidone.Results: The average age of patients experiencing their first episode of SZ was 29.7± 6.6 years, and 23 (46%) were men. The initial sICAM-1 levels of the patients were lower than those of the control group (P< 0.0001), and increased after treatment (P=0.02), but remained lower than in the healthy controls (P=0.026). The initial levels of sVCAM-1 levels were higher in the patients (P< 0.0001) and decreased after treatment (P< 0.0001) to values that were similar to those of the control group (P=0.39). The only independent predictor of a baseline BPRS over 120 was the baseline sVCAM-1 level (P< 0.0001). Antipsychotic treatment induced significant decreases in BPRS score (P< 0.0001), in systolic (P=0.005) and diastolic (P< 0.0001) blood pressure, in HDL-c (P=0.02), as well as significant increases in blood glucose (P< 0.01) and LDL-c (P< 0.001), with no differences between olanzapine and risperidone.Conclusion: In the patients experiencing an FEP of SZ, the levels of sICAM-1 were lower, while the levels of sVCAM-1 were higher than in the healthy control subjects. The antipsychotics used in the treatment of schizophrenia increased sICAM-1 and decreased sVCAM. The baseline level of sVCAM-1 was an independent predictor of a BPRS score > 120 at baseline.Keywords: sICAM-1, sVCAM-1, schizophrenia, inflammation, atherosclerosis, cardiac dysfunction